2020
DOI: 10.1111/epi.16482
|View full text |Cite
|
Sign up to set email alerts
|

Focal and generalized seizure activity after local hippocampal or cortical ablation of NaV1.1 channels in mice

Abstract: Early onset seizures are a hallmark of Dravet syndrome. Previous studies in rodent models have shown that the epileptic phenotype is caused by loss‐of‐function of voltage‐gated NaV1.1 sodium channels, which are chiefly expressed in γ‐aminobutyric acid (GABA)ergic neurons. Recently, a possibly critical role has been attributed to the hippocampus in the seizure phenotype, as local hippocampal ablation of NaV1.1 channels decreased the threshold for hyperthermia‐induced seizures. However, the effect of ablation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
3
14
0
1
Order By: Relevance
“…This evidence suggests that disease progression by a febrile seizure can occur independent of developmental stages, and that the exacerbation of phenotype is not solely a developmental defect, but likely involves a proexcitatory plasticity mechanism. This is consistent with studies demonstrating that postnatal Scn1a deletion can create an epileptic encephalopathy similar to the genomic model 32,33 , and also that the disease phenotype can be reversed or ameliorated when Scn1a expression is recovered at a juvenile age 3436 . These findings suggest a life-long risk of exacerbation of disease to severe epilepsy encephalopathy, but also a potential for reversal of disease if the underlying mechanism can be appropriately targeted.…”
Section: Discussionsupporting
confidence: 91%
“…This evidence suggests that disease progression by a febrile seizure can occur independent of developmental stages, and that the exacerbation of phenotype is not solely a developmental defect, but likely involves a proexcitatory plasticity mechanism. This is consistent with studies demonstrating that postnatal Scn1a deletion can create an epileptic encephalopathy similar to the genomic model 32,33 , and also that the disease phenotype can be reversed or ameliorated when Scn1a expression is recovered at a juvenile age 3436 . These findings suggest a life-long risk of exacerbation of disease to severe epilepsy encephalopathy, but also a potential for reversal of disease if the underlying mechanism can be appropriately targeted.…”
Section: Discussionsupporting
confidence: 91%
“…Using this tool, we have found that the need for homogeneous and widespread transgene expression is not as stringent as predicted in DS. The hippocampus is considered an important target for this disease, 34,35 but we found that HAdV5 vectors administered in this location reached a relatively low number of neurons and did not transduce neighboring structures. Injection in the cortex obtained efficient but locally restricted transgene expression, while cerebellum and especially basal ganglia were more permissive for vector transduction, in agreement with previous reports.…”
Section: Discussionmentioning
confidence: 76%
“…Remarkably, a mutation in SCN1A , voltage-gated sodium channel alpha subunit 1 (VGSC), causes over 80% of Dravet syndrome cases [ 40 , 243 ]. Several knockout rodent models have been generated for Dravet syndrome [ 244 , 245 ], whereas zebrafish homozygous scn1lab −/− mutants have also been used as an epilepsy model [ 246 ]. Except for α subunit, β subunit ( Scn1b ), type 2 ( Scn2a ), and type 8 ( Scn8a ) have also been used as genetic models for epilepsy in mice.…”
Section: Animal Models For Epilepsiesmentioning
confidence: 99%